2000
DOI: 10.1007/bf02703624
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of organised disturbances in fully developed turbulent channel flow

Abstract: In our earlier work we have shown the relevance of stability theory in understanding the sustenance of turbulence in turbulent boundary layers. Here we adopt the same model to study the evolution of organised disturbances in turbulent channel flow. Since the dominant modes are wall modes we find that the stability characteristics in the two flows are nearly identical although the boundary conditions (at the edge of the boundary layer and at the centre of the channel) are different. Comparisons with the experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(41 citation statements)
references
References 18 publications
3
38
0
Order By: Relevance
“…However, they did not find any region of instability in their theoretical work and this was confirmed by their experiments . Sen & Veeravalli (1998, 2000a) (hereinafter referred to as SV1 and SV2 respectively) considered the problem afresh and concluded that the main reason that the previous investigators failed to find any unstable modes was that they used an isotropic eddy viscosity model, which is really not justified close to the wall. They then derived an extended Orr-Sommerfeld equation based on an anisotropic eddy viscosity model (the eddy viscosity model is similar to the one outlined in Pope 1975).…”
Section: Introductionmentioning
confidence: 98%
“…However, they did not find any region of instability in their theoretical work and this was confirmed by their experiments . Sen & Veeravalli (1998, 2000a) (hereinafter referred to as SV1 and SV2 respectively) considered the problem afresh and concluded that the main reason that the previous investigators failed to find any unstable modes was that they used an isotropic eddy viscosity model, which is really not justified close to the wall. They then derived an extended Orr-Sommerfeld equation based on an anisotropic eddy viscosity model (the eddy viscosity model is similar to the one outlined in Pope 1975).…”
Section: Introductionmentioning
confidence: 98%
“…Experimental results are based on Sen & Veeravalli [6][7], hence a brief outline of the theory is directly reproduced from Sen & Veeravalli [7] to provide the background in which the experimental results may be interpreted. For the stability analysis the base flow is fully developed turbulent channel flow.…”
Section: Sen and Veeravalli [7] Theoretical Formulationmentioning
confidence: 99%
“…Their experiments (Hussain & Reynolds,[5]) and theoretical results indicated that hydrodynamic stability theory may not be relevant to wallturbulence. Sen & Veeravalli [6][7] considered the problem afresh and concluded that the inability of previous researchers to find any unstable modes was because of the selection of an isotropic eddy viscosity model, which is really not justified near the wall. Sen & Veeravalli [6][7] used a more realistic anisotropic eddy viscosity model (based on Pope, [8]) and found wall-mode instabilities.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations